The difference of salivary pH before and after toothbrushing with toothpaste containing Betel leaf (Piper Betle) - Fu, Soo Ling; Kintawati, Silvi; Tjahajawati, Sri (Universitas Padjadjaran, 2014)
There has been a long history of the use of plants to improve dental health and oral hygiene. The purpose of this research was to find out the difference of salivary pH before and after toothbrushing with toothpaste containing betel leaf (Piper betel). The type of research used was quasi-experimental. Data collected were analyzed by using a paired t-test. The result shows that there is an increase of salivary pH by an average of 0.48 after toothbrushing with toothpaste containing betel leaf (Piper betel). In conclusion, there is the difference between the salivary pH before and after toothbrushing with toothpaste containing betel leaf (Piper betel).